automorphisms of association schemes whose relations are
play

Automorphisms of association schemes whose relations are of valency - PDF document

Automorphisms of association schemes whose relations are of valency one or three Mitsugu Hirasaka Department of Mathematics Pusan National University Joint Work with Jeong Rye Park June 2-5, 2014 Modern Trends in Algebraic Graph Theory at


  1. Automorphisms of association schemes whose relations are of valency one or three Mitsugu Hirasaka Department of Mathematics Pusan National University Joint Work with Jeong Rye Park June 2-5, 2014 Modern Trends in Algebraic Graph Theory at Villanova University, Villanova, Pennsilvania 1

  2. Notations for association schemes X : a finite set ( X, { R i } d i =0 ) : an association scheme { A i } d i =0 : the set of adjacency matrices A 0 = I , A T i = A i ′ , A i A j = � d i =0 p k ij A k , k i = p 0 ii ′ : the valency of R i R i ( x ) = { y ∈ X | ( x, y ) ∈ R i } . X : a finite set ( X, S ) where S is a partition of X × X { σ s | s ∈ S } : the set of adjacency matrices σ 1 = I , σ ∗ s = σ s ∗ , σ s σ t = � u ∈ S a stu σ u , n s = a ss ∗ 1 : the valency of s , xs = { y ∈ X | ( x, y ) ∈ s } . 2

  3. In this talk we assume that S # = S \ { 1 } , N ( S ) = { n s | s ∈ S # } , and we shall write s · t = � u ∈ S a stu u instead of σ s σ t = � u ∈ S a stu σ u , and st = { u ∈ S | a stu > 0 } . r : X × X → S , ( x, y ) �→ r ( x, y ) where ( x, y ) ∈ r ( x, y ). Aut( X, S ) = { ρ ∈ Sym ( X ) | ∀ x, y, r ( x, y ) = r ( x ρ , y ρ ) } . An orbital means an orbit of the induced action of G on X × X where G ≤ Sym ( X ). We say that ( X, S ) is regular if S is the set of orbitals of a regular group. We say that ( X, S ) is Frobenius if S is the set of orbitals of a Frobenius group. We say that ( X, S ) is schurian if S is the set of orbitals of a transitive group. 3

  4. Known Results N ( S ) = { k } (called k -equivalenced). 1. N ( S ) = { 1 } . For example,         1 0 0 0 1 0 0 0 1     0 1 0 0 0 1 1 0 0  ,  ,           0 0 1 1 0 0 0 1 0     Theorem. ([Zieschang, 1996]) N ( S ) = { 1 } ⇐ ⇒ ( X, S ) is regular. 2. N ( S ) = { 2 } . For example,         1 0 0 0 0 0 1 0 0 1 0 0 1 1 0       0 1 0 0 0 1 0 1 0 0 0 0 0 1 1                           0 0 1 0 0 , 0 1 0 1 0 , 1 0 0 0 1             0 0 0 1 0 0 0 1 0 1 1 1 0 0 0                       0 0 0 0 1 1 0 0 1 0 0 1 1 0 0     Theorem. ([Muzychuk, Zieschang, 2008]) N ( S ) = { 2 } ⇒ ( X, S ) is Frobenius. 4

  5. 3. N ( S ) = { 3 } . For example, { Cay ( F 7 , { 0 } ) , Cay ( F 7 , { 1 , 2 , 4 } ) , Cay ( F 7 , { 2 , 5 , 6 } ) } Theorem. (see [H, Kyoung-Tark Kim, Jeong Rye Park, 2014]) N ( S ) = { 3 } ⇒ ( X, S ) is Frobenius. 4. N ( S ) = { 4 } . For example, H (2 , 3) : the Hamming scheme Theorem. ([Jeong Rye Park, 2014]) N ( S ) = { 4 } ⇒ Aut( X, S ) is transitive. 5. N ( S ) = { k } . For example, Cyclotomic schemes of valency k Theorem. (see [Muzychuk, Ponomarenko, 2011]) Suppose N ( S ) = { k } , ∀ s ∈ S # , � t ∈ S a s tt ∗ = k − 1. If | S | ≥ 4( k − 1) k 3 then ( X, S ) is Frobenius. 5

  6. 6. N ( S ) = { 1 , 2 } (called quasi-thin). For example, The set of orbitals of the action of G on G/H where | H | = 2. Lemma. ([H, Muzychuk, 2002]) Suppose N ( S ) = { 1 , 2 } . For x ∈ X , φ x : X → X, y �→ y ′ where yr ( x, y ) = { y, y ′ } is an element of Aut( X, S ). Remark. (see [Hanaki, Miyamoto], and [M.Klin, M.Muzychuk, C.Pech, A.Woldar, P.-H.Zieschang] ) (1) as16-173 is a non-schurian quasi-thin scheme. (2) as28-176 is a non-schurian quasi-thin scheme. Theorem. ([Muzychuk, Ponomarenko, 2012]) Suppose N ( S ) = { 1 , 2 } . If ( X, S ) is not schurian then ( X, S ) is a Kleinian scheme of index 4 or 7. 6

  7. Our Main Focus N ( S ) = { 1 , 3 } . For example, The set of orbitals of the action of G on G/H where | H | = 3. Remark. ([Hanaki, Miyamoto]) (1) as27-473 is a non-schurian scheme; (2) as27-475 is a non-schurian scheme; (3) as27-477 is a non-schurian scheme. We wish to find a non-trivial automorphism with a fixed point. For the remainder of this talk we assume that ( X, S ) is an association scheme with N ( S ) = { 1 , 3 } . We define τ : S → Z ≥ 0 such that τ ( s ) = max { a ss ∗ u | u ∈ S # } for s ∈ S . (1) For s, t ∈ S , n s n t = � u ∈ S a stu n u ∈ { 1 , 3 , 9 } and lcm( n s , n t ) | a stu n u ; (2) τ ( s ) = 0 ⇐ ⇒ n s = 1 and S = τ − 1 (0) ∪ τ − 1 (1) ∪ τ − 1 (2) ∪ τ − 1 (3); (3) For s ∈ τ − 1 (1) ∪ τ − 1 (2) and t ∈ S there exists u ∈ S such that a tu ∗ s = 1; (4) For s ∈ S , τ ( s ) = τ ( s ∗ ). 7

  8. Please watch a movie on the white board. Fix x ∈ X . We define Γ x to be { ρ ∈ Sym ( X ) | ∀ t ∈ S, xt is an orbit of � ρ � } . For ρ ∈ Γ x we define a binary relation ∼ ρ on S such that s ∼ ρ t if and only if r ( y, z ) = r ( y ρ , z ρ ) for each ( y, z ) ∈ xs × xt . Lemma 1. For ρ ∈ Γ x , ∼ ρ is the trivial equiva- lence relation if and only if ρ ∈ Aut( X, S ). Lemma 2. For s ∈ τ − 1 (1) ∪ τ − 1 (2) there exists ρ ∈ Γ x such that s ∼ ρ t for each t ∈ S and u ∼ ρ v for all u, v ∈ S with n u n v ≤ 3. Theorem. Suppose u ∼ ρ v , u ∼ ρ w , v ≁ ρ w and u ∈ τ − 1 (1) ∪ τ − 1 (2) for v, w ∈ S \ τ − 1 (0). Then we have the following: (1) ( X, S ) is not commutative; (2) For s ∈ uu ∗ \ { 1 } , τ ( s ) = 3. 8

  9. Sketch of the Proof s ∈ S α s ¯ Define � � s ∈ S α s s, � s ∈ S β s s � := � β s n s . Key Lemma. For all a, b, c ∈ S \ τ − 1 (0) with b � = c and ab ∩ ac � = ∅ we have the following: (1) If τ ( a ) = τ ( b ) = 3 then cb ∗ ⊆ τ − 1 (0), (2) If τ ( a ) = 1 and b ∗ b = c ∗ c ⊆ τ − 1 (0) then c · b ∗ = 3 d for some d ∈ a ∗ a with τ ( d ) = 3. (Proof) Note that 0 < � a · b, a · c � = � a ∗ · a, c · b ∗ � = � a ∗ · a − 3 · 1 , c · b ∗ � . (1) τ ( a ∗ ) = τ ( a ) = 3 implies that c = t · b for some t ∈ a ∗ a ∩ τ − 1 (0). Since τ ( b ) = 3, cb ∗ = ( tb ) b ∗ ⊆ τ − 1 (0). (2) By the assumption, � c · b ∗ , c · b ∗ � = � c ∗ · c, b ∗ · b � = 27. This implies that c · b ∗ = 3 d for some d ∈ a ∗ a with d ∈ τ − 1 (3). 9

  10. Please watch a movie on the white board. Suppose that | u ∗ v | = | u ∗ w | = | v ∗ w | = 3, ( u ∗ v ∪ u ∗ w ∪ v ∗ w ) ∩ τ − 1 (0) = ∅ u ∗ v = { a 0 , a 1 , a 2 } , u ∗ w = { b 0 , b 1 , b 2 } , v ∗ w = { c 0 , c 1 , c 2 } . By the assumption on ∼ ρ , we have a ∗ i · b j = c 0 + c 1 + c 2 for all i, j ∈ { 0 , 1 , 2 } ; a i · c j = b 0 + b 1 + b 2 for all i, j ∈ { 0 , 1 , 2 } ; b i · c ∗ j = a 0 + a 1 + a 2 for all i, j ∈ { 0 , 1 , 2 } . s ∈ S α s ¯ Recall � � s ∈ S β s s � := � s ∈ S α s s, � β s n s . Lemma 4. We have � b i · b ∗ i , a j · a ∗ k � = � a ∗ j · b i , a ∗ k · b i � = 9, τ ( a i ) � = 2 and � b ∗ i · b i , a ∗ k · a j � = � b ∗ i · b i − 3 · 1 , a ∗ k · a j � if j � = k . Lemma 5. For s, t ∈ S \ τ − 1 (0), s · s ∗ = t · t ∗ ⇐ ⇒ � t ∗ · s, t ∗ · s � > 9. 10

  11. Lemma 6. We have a 1 · a ∗ 1 = a 2 · a ∗ 2 = a 3 · a ∗ 3 , b 1 · b ∗ 1 = b 2 · b ∗ 2 = b 3 · b ∗ 3 , c 1 · c ∗ 1 = c 2 · c ∗ 2 = c 3 · c ∗ 3 , a ∗ 1 · a 1 = a ∗ 2 · a 2 = a ∗ 3 · a 3 , b ∗ 1 · b 1 = b ∗ 2 · b 2 = b ∗ 3 · b 3 , c ∗ 1 · c 1 = c ∗ 2 · c 2 = c ∗ 3 · c 3 , (Proof for the first case) Recall b ∗ i · a ∗ j = c 0 + c 1 + c 2 for all i, j ∈ { 0 , 1 , 2 } ; τ ( b ∗ i ) � = 2 since � b ∗ i · b i − 3 · 1 , a ∗ k · a j � = 9. i · b i = 3 · 1+ d + d ∗ for some d ∈ If τ ( b ∗ i ) = 1, then b ∗ S \ τ − 1 (0). Since a ∗ k · a j ∈ { d +2 d ∗ , 2 d + d ∗ , 3 d, 3 d ∗ } for all distinct j , k , we have � a ∗ k · a j , a ∗ k · a i � > 9 for each case. Therefore, Lemma 6 follows from Lemma 5. i · b i = 3 · 1 + 3 t + 3 t ∗ for some If τ ( b ∗ j ) = 3, then b ∗ t ∈ τ − 1 (0), and hence a j ∈ { a j · t, a k · t ∗ } , implying j = ( a k · t ) · ( t ∗ · a k ) = a k · a ∗ a j · a ∗ k . 11

  12. Lemma 7. We have ( τ ( a i ) , τ ( b i )) ∈ { (1 , 3) , (3 , 1) } , (Proof) By Lemma 4, 2 / ∈ { τ ( a i ) , τ ( b i ) , τ ( b i ) } . Thus, it suffices to exclude the cases ( τ ( a i ) , τ ( b i )) ∈ { (1 , 1) , (3 , 3) } . Suppose ( τ ( a i ) , τ ( b i )) = (1 , 1), Then a j · a ∗ k ∈ { e + 2 e ∗ , 2 e + e ∗ } where b i · b ∗ i = 3 · 1 + e + e ∗ . This implies that � a i · a ∗ j , a i · a ∗ k � = � a ∗ i · a i , a ∗ k · a j � ≥ 12, which contradicts τ ( a ∗ i ) = τ ( a i ) = 1. Suppose ( τ ( a i ) , τ ( b i )) = (3 , 3), Then t ∈ a j a ∗ k where b i · b ∗ i = 3 · 1 + 3 t + 3 t ∗ . Since τ ( a j ) = 3 and a j = t · a k , a j a ∗ k ⊆ τ − 1 (0). Since u ∗ u ∩ a j a ∗ k � = ∅ , it contradicts τ ( u ) ∈ { 1 , 2 } . Without loss of generality we may assume that ( τ ( a i ) , τ ( b i )) = (1 , 3). By Key Lemma, τ ( d ) = 3 where d ∈ u ∗ u ∩ b 1 b ∗ 2 . Thus, the first second statement of Theorem is proved. Suppose that ( X, S ) is commutative. Then d ∈ u ∗ u ∩ b 1 b ∗ 2 = b ∗ 2 b 1 ⊆ τ − 1 (0) since τ ( b i ) = τ ( b ∗ i ) = 3, a contradiction. This completes the theorem. 12

Recommend


More recommend